Saleh A. R. Al-Mezel, Falleh R. M. Al-Solamy and Qamrul H. Ansari, Fixed Point Theory, Variational Analysis, and Optimization, CRC Press, Taylor & Francis Group, Boca Raton 2014, xx + 347 pp, ISBN: 13: 978-1-4822-2207-4. - KOLUMBÁN, J. (Studia Universitatis Babeș-Bolyai Mathematica, 2015)
The present volume grew out of an International Workshop on Nonlinear Anal- ysis and Optimization, held at the University of Tabuk, Saudi Arabia, March 16-19, 2013, most of the contributors being participants to this event. It is divided into three parts: I. Fixed point theory; II. Convex analysis and variational analysis, and III. Vector optimization.